Psychological factors as risk factors for poor hip function after total hip arthroplasty - Benditz A; Jansen P; Schaible J; Roll C; Grifka J; Götz J (Dove Medical Press, 2017)
Achim Benditz,1 Petra Jansen,2 Jan Schaible,1 Christina Roll,1 Joachim Grifka,1 Jürgen Götz1 1Department of Orthopedics, University Medical Center Regensburg, Asklepios Klinikum Bad Abbach, Bad Abbach, 2Department of Sport Science, University of Regensburg, Regensburg, Germany Abstract: Recovery after total hip arthroplasty (THA) is influenced by several psychological aspects, such as depression, anxiety, resilience, and personality traits. We hypothesized that preoperative depression impedes early functional outcome after THA (primary outcome measure). Additional objectives were perioperative changes in the psychological status and their influence on perioperative outcome. This observational study analyzed depression, anxiety, resilience, and personality traits in 50 patients after primary unilateral THA. Hip functionality was measured by means of the Harris Hip Score. Depression, state anxiety, and resilience were evaluated preoperatively as well as 1 and 5 weeks postoperatively. Trait anxiety and personality traits were measured once preoperatively. Patients with low depression and anxiety levels had significantly better outcomes with respect to early hip functionality. Resilience and personality traits did not relate to hip functionality. Depression and state anxiety levels significantly decreased within the 5-week stay in the acute and rehabilitation clinic, whereas resilience remained at the same level. Our study suggests that low depression and anxiety levels are positively related to early functionality after THA. Therefore, perioperative measurements of these factors seem to be useful to provide the best support for patients with risk factors. Keywords: total hip arthroplasty, psychological factors, depression, state anxiety, trait anxiety, resilience, personality traits